Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2007
DOI: 10.2224/sbp.2007.35.2.195
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral Profiles of Different Types of Social Status in Preschool Children: An Observational Approach

Abstract: The authors wish to thank E. Collado for his help in the data analysis and for his comments. They would also like to thank the Head and teachers of the Escuela Josefina Pascual de Cádiz and the parents who enabled them to undertake the observations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 48 publications
(55 reference statements)
1
9
0
1
Order By: Relevance
“…Reviewing this finding, and other research, Pellegrini and Blatchford (2000) concluded that 'children's breaktime, or recess, does have educational implications' (p. 75). A later attempt to explore some of these issues (Braza et al, 2007) concluded:…”
Section: No Space To Play At Homementioning
confidence: 99%
“…Reviewing this finding, and other research, Pellegrini and Blatchford (2000) concluded that 'children's breaktime, or recess, does have educational implications' (p. 75). A later attempt to explore some of these issues (Braza et al, 2007) concluded:…”
Section: No Space To Play At Homementioning
confidence: 99%
“…Previous studies have indicated that children's peer relationships correlate with their behavioural and emotional characteristics (e.g., Bierman, 2004;Braza et al 2007;Coie, Dodge, and Coppotelli 1982;Coie, Dodge, and Kupersmidt 1990;Newcomb, Bukowski, and Pattee 1993). A major focus of peer relationships research has largely been on children's deficits, problems, and pathologies, for example, in aggressive behaviour (e.g., Faris and Ennett 2012;Rodkin and Berger 2008;Pellegrini and Long 2008), depressive symptoms (e.g., Blöte et al 2012;Teunissen et al 2011;Bell-Dolan, Foster, and Christopher 1995), and learning disabilities (Kiuru et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…1993). They have less aggressive/disruptive behaviour (Braza et al 2007;Coie et al 1982, Newcomb et al 1993) and depressive symptoms (Teunissen et al 2011). Especially prosocial behaviour (e.g., helping, cooperating, and sharing with peers) correlates strongly with peer acceptance, positive peer interaction, and better peer relationships (Clark and Ladd 2000;Coie et al 1982;Newcomb et.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Populiarumas klasėje buvo vertintas prašant tiriamo vaiko iš tyrime dalyvaujančių klasės vaikų sąrašo nurodyti tris bendraklasius, su kuriais jis labiausiai norėtų draugauti (paaiškinant, kad galima rinktis ir tą vaiką, su kuriuo draugauji ir šiuo metu). Šis metodas buvo pasirinktas remiantis kitų autorių (Banerjee, Carolien, Meerum, Gerlein ir Voustina, 2006;Braza et al, 2007;Mestre, Guil, Lopes, Salovey ir Gil-Olarte, 2006) ankstesniuose tyrimuose naudotais populiarumo tarp bendraamžių įvertinimo principais, kai tiriamųjų būdavo prašoma įvardyti tris geriausius draugus ar nurodyti, su kuriais trimis bendraamžiais labiausiai norėtų žaisti. Tiriamojo populiarumo įvertis buvo skaičiuojamas pagal jį pasirinkusių tiriamųjų dažnį bei padalijant tą skaičių iš visų tyrimo dalyvių skaičiaus ir atėmus vieną (taip neįtraukiant tiriamojo, kurio populiarumo balas skaičiuojamas).…”
Section: Populiarumas Klasėjeunclassified